Finite Element Model to Predict the Impact of Wrinkles on Wind Turbine Blades. Issue 3 (1st May 2022) - Mendonça, Heloisa Guedes; Mikkelsen, Lars Pilgaard; Branner, Kim
Abstract: Among the manufacturing defects of wind turbine blades, wrinkles are critical to the blade performance, affecting the structural integrity. Therefore, this paper introduces three-dimensional numerical models of laminates representative of a wind turbine blade with artificial wrinkles. The models are verified against static tension-compression experimental tests of laminates embedded with two types of wrinkles. The results show a good correlation between numerical prediction and experimentally obtained stiffness behaviour. The outcome of this analysis proves the validity of the numerical modelling strategy applied to evaluate the behaviour of laminates with wrinkles for a static loading situation.